VALIDATED RP-UPLC METHOD DEVELOPMENT FOR ESTIMATION OF LANSOPRAZOLE IN TABLET DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
A simple, sensitive and precise isocratic ultra performance liquid chromatographic method for the analysis of Lansoprazole has been developed, validated and used for the determination of compounds in commercial pharmaceutical products. The separation was carried out isocratically on a C18 column utilizing a mobile phase consisting of methanol: water (80:20 v/v) at a flow rate of 1.0 mL/min with UV detection at 284 nm. The retention time of Lansoprazole was found to be 3.905 min. The described method was linear over a concentration range of 50-30 μg/ml (r2 =0∙998) for the assay of Lansoprazole. Results of analysis were validated statistically. The results of the study showed that the proposed RP-UPLC method is simple, rapid, precise and accurate, which is useful for the routine determination of Lansoprazole in tablet dosage form and in its pharmaceutical dosage forms.